Caring for a family member with intellectual disability into old age: Applying the sociocultural stress and coping model to Italian and Greek migrants in Australia. Issue 5 (18th February 2020) - Walker, Ruth; Belperio, Irene; Gordon, Sally; Hutchinson, Claire; Rillotta, Fiona
Abstract: Background: Little is known about how older parent caregivers from culturally and linguistically diverse (CALD) backgrounds experience caring for their family member with intellectual disability into late life. Method: In‐depth semi‐structured interviews were carried out with N = 19 family caregivers aged 50–91 from ten Italian and four Greek families. The Sociocultural Stress and Coping Model was used as a framework to interpret their experiences. Results: A number of stressors including the need to make sacrifices, physical and emotional demands, uncertain futures and challenges associated with "the system" were identified. While family members play a key role in providing support, changing values around filial responsibility were evident. Discussion: Further attention needs to be given to CALD families to address challenges associated with caring for their family member with intellectual disabilities as they age. This study also challenges assumptions that CALD families prefer to keep caring within the family long‐term.